Comparison of transcranial magnetic stimulation measures obtained at rest and under active conditions and their reliability - Ngomo, Suzy; Leonard, Guillaume; Moffet, Hélène; Mercier, Catherine (Journal of neuroscience methods, 2012)
► Resting and active motor threshold (MT) show a linear relationship. ► Resting and active maps are similar when differences in MT are taken into account. ► Most of the TMS measures present good reliability under the appropriate condition. ► Most of the TMS measures present comparable short-term and long-term reliability. Transcranial magnetic stimulation (TMS) studies investigating motor cortex reorganization in clinical populations use a variety of measurements, with some performed at rest and others with the muscle slightly contracted. Surprisingly there are still a limited number of studies focusing on relationship between TMS-measures obtained at rest and during active muscle contraction in healthy individuals. The purpose of this study was to: (1) compare resting and active TMS-measures and assess their association; (2) determine their respective short- and long-term reliability. Motor threshold (MT), motor evoked potentials (MEP) amplitude, map area, normalized map volume, map center of gravity (CoG) and short-interval intracortical inhibition (SICI) of the first dorsal interosseous (FDI) muscle were assessed in 12 healthy subjects. Subjects were tested three times (with a short (four days) and a long (>1 month) inter-session interval). No significant difference was found between resting and active measures, except for MT. Active MT was on average at 82% of resting MT. Good short- and long-term reliability were found for MT and CoG (in resting and active conditions), for the SICI and MEP amplitude at rest and for the normalized map volume under active condition. In conclusion, maps of FDI muscle obtained at rest and during active contraction are very similar to each other in healthy individuals when differences in MT are taken into account. Most TMS measures present good reliability when obtained under the appropriate condition, with comparable short-term and long-term reliability.